Influence of Vibrational Treatment on Thermomechanical Response of Material under Conditions Identical to Friction Stir Welding - Konovalenko I. S. Ivan Sergeevich; Konovalenko I. S. Igor Sergeevich; Dmitriev A. I. Andrey Ivanovich; Psakhie S. G. Sergey Grigorievich; Kolubaev Е. А. Evgeny Aleksandrovich (2015, 2015)
Title screen